Fatigue in living kidney donors compared to a German general population sample: an exploratory study - Dilek Akkus; Adrian Westenberger; Gunilla Einecke; Gunilla Einecke; Wilfried Gwinner; Uwe Tegtbur; Mariel Nöhre; Martina de Zwaan (Frontiers in Psychiatry)
BackgroundClinical studies have not conclusively clarified whether fatigue scores in living kidney donors after donation are fundamentally different from general population samples. Moreover, the association between sociodemographic and donor specific factors and fatigue in donors is not well understood.Patients and methodsFatigue scores of 358 living kidney donors on average 7.67 years post-donation were compared with 1896 subjects from the German general population in five strata of age and sex. Fatigue was measured with the Multidimensional Fatigue Inventory (MFI-20). Relationships between the five MFI-20 subscales and the sociodemographic variables sex, age, education, and in the donor sample also years since donation were calculated. Additionally, the association between donor specific variables and fatigue levels were analyzed.ResultsOverall, donors had lower fatigue scores than the population sample. Particularly the age group 65-74 and above reported significantly lower fatigue scores. A significant exception was found in women aged 45-54 years, where donors showed significant higher general fatigue scores than the corresponding subgroup of the general population sample. Multiple regression analyses in the general population sample revealed associations between female sex and higher age with higher values in most MFI-20 subscales, whereas subjects with higher education showed mostly lower fatigue scores. In the donor group, these associations were of little importance. Also, years since donation, partnership, and recipient group were not strongly related to fatigue. However, higher fatigue in donors was associated with more donation regret, a more negative relationship with the recipient, a more negatively perceived recipient health, less perceived family support, and more financial burden.ConclusionFatigue is less prevalent particularly in older donors and predictors of fatigue presented in the general population sample seem to have little importance in the donors. However, middle-aged female donors might be more prone to develop fatigue. This group may require more intense exploration before and after donation to detect and treat the underlying factors timely.